Sinergi Kolaboratif dalam Pendidikan Islam: Analisis Konseptual Tentang Kerja Tim dan Pengelolaan Sumber Daya Manusia - Trimurniyati, Pera; Kurniati, Yeli; Jamilus , Jamilus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to conceptually analyze the role and urgency of teamwork in managing human resources within Islamic educational institutions. The research employs a library research approach by reviewing scholarly sources including journals, books, and recent research reports relevant to educational management and Islamic values. The findings indicate that teamwork in Islamic education encompasses interrelated spiritual, moral, and professional dimensions. The Islamic values of syura (consultation), ukhuwah (brotherhood), ta‘awun (mutual assistance), and amanah (trustworthiness) serve as the ethical foundation for building collaborative synergy among educators and administrative staff. Teamwork plays a crucial role in enhancing organizational effectiveness, strengthening Islamic work culture, and developing the professional competence of educators. Moreover, transformational leadership grounded in Islamic values contributes significantly to creating productive and harmonious teams that are aligned with educational and spiritual visions. In the digital era, teamwork should be adapted through the integration of communication technology and online collaborative learning without neglecting the spiritual essence of Islam